Community marketplace mobile application / Muhammad Na’im Mohammad Hatta - Mohammad Hatta, Muhammad Na’im (2022)
Interaction and the socioeconomic gap between neighbours inside neighbourhood communities become less especially in urban and suburban areas. This work presents one of the solving methods to improve social able interaction inside the community. By introducing the Community Marketplace Mobile Application, it is designed to increase the interaction between neighbours and improve the socioeconomic of the community. The benefit of using modern devices like a smartphone to improve the social interaction and economy of the community is developed and studied. Being developed based on Kotlin which is one of the main languages of building apps on Android. The reason for the development of the app for Android OS is that most people are using it more than other operating systems. System Development Life Cycle (SDLC) Waterfall model was chosen as the development method for this project due to the limited timeframe and the most suitable with the process of the development of the project. Bar charts and tables of results from User Acceptance Test (UAT) questions are being presented. Based on the result, most of the respondents strongly agreed that the mobile app can increase their interaction with their neighbours and also help their neighbours to improve the neighbour business and economy. The Community Marketplace Mobile Application achieved the project objectives: to design a system where customers can set their ideal distances or community from where they want to purchase and develop a platform where all of the residents of a community can gather and discuss any issues about their community.